2016
DOI: 10.1016/j.psyneuen.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Trait positive and negative emotionality differentially associate with diurnal cortisol activity

Abstract: Summary Inter-individual variability in metrics of hypothalamic-pituitary-adrenocortical (HPA) activity, such as the slope of the diurnal decline in cortisol, cortisol awakening response (CAR), and total cortisol output, have been found to associate inversely with trait ratings of extraversion and positive affect (E/PA) and positively with neuroticism and negative affect (N/NA) in some, but not all, investigations. These inconsistencies may partly reflect varied intensity of cortisol sampling among studies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 54 publications
6
17
0
1
Order By: Relevance
“…While both negative affect and reduced perceived control are painful experiences, perceived control is considered a fundamental human need and may be more likely to invoke concerns that lead to hypo-pituitary-adrenocortical response, an evolutionary neurobiological sensitivity to threat of self-preservation, safety, and goal attainment (Broman et al, 2000;Brondolo et al, 2018;Dickerson & Kemeny, 2004;Williams & Mohammed, 2009). Research on diurnal cortisol typically includes negative affect and depression (e.g., Adam et al, 2017;Miller et al, 2016), but the few studies that capture positive wellbeing, such as trait control, show that it is associated with healthier cortisol rhythms (Cohen et al, 2006;Miller et al, 2016). The present results highlight the importance of reduced perceived control as a health risk pathway due to discrimination against Blacks and are important in the greater research conversation surrounding wellbeing, including autonomy and mastery, as essential to healthy neuroendocrine functioning (Steptoe, 2019).…”
Section: Racial Exclusion Is Associated With Cortisol Releasementioning
confidence: 99%
“…While both negative affect and reduced perceived control are painful experiences, perceived control is considered a fundamental human need and may be more likely to invoke concerns that lead to hypo-pituitary-adrenocortical response, an evolutionary neurobiological sensitivity to threat of self-preservation, safety, and goal attainment (Broman et al, 2000;Brondolo et al, 2018;Dickerson & Kemeny, 2004;Williams & Mohammed, 2009). Research on diurnal cortisol typically includes negative affect and depression (e.g., Adam et al, 2017;Miller et al, 2016), but the few studies that capture positive wellbeing, such as trait control, show that it is associated with healthier cortisol rhythms (Cohen et al, 2006;Miller et al, 2016). The present results highlight the importance of reduced perceived control as a health risk pathway due to discrimination against Blacks and are important in the greater research conversation surrounding wellbeing, including autonomy and mastery, as essential to healthy neuroendocrine functioning (Steptoe, 2019).…”
Section: Racial Exclusion Is Associated With Cortisol Releasementioning
confidence: 99%
“…Positive affect, in turn, has been linked to cortisol, although previous findings have been inconsistent. When comparing between-persons, findings from several studies suggest that people with higher trait-like or aggregated momentary positive affect had smaller CAR than those with lower positive affect (Brummett et al, 2009; Chida and Steptoe, 2009; Miller et al, 2016; Steptoe et al, 2007). Greater positive affect has been associated with steeper diurnal slopes between-persons (Hoyt et al, 2015; Miller et al, 2016), but null results have also been reported for diurnal slopes (Brummett et al, 2009; Slatcher et al, 2015), CAR (Hoyt et al, 2015), AUC (Miller et al, 2016), and cortisol levels averaged across a day (Steptoe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…When comparing between-persons, findings from several studies suggest that people with higher trait-like or aggregated momentary positive affect had smaller CAR than those with lower positive affect (Brummett et al, 2009; Chida and Steptoe, 2009; Miller et al, 2016; Steptoe et al, 2007). Greater positive affect has been associated with steeper diurnal slopes between-persons (Hoyt et al, 2015; Miller et al, 2016), but null results have also been reported for diurnal slopes (Brummett et al, 2009; Slatcher et al, 2015), CAR (Hoyt et al, 2015), AUC (Miller et al, 2016), and cortisol levels averaged across a day (Steptoe et al, 2007). Findings are also equivocal at the within-person level, such that state positive affect has been linked to lower-than-usual momentary salivary cortisol levels (i.e., cortisol reactivity) (Smyth et al, 1998) and lower same-day AUC (Nater et al, 2010; Polk et al, 2005), whereas other studies have found no associations of state positive affect with cortisol reactivity (Jacobs et al, 2007; van Eck et al, 1996) or the diurnal rhythm (Adam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…People with higher trait positive affect are more likely to show a steeper decrease in salivary cortisol across the day, compared to those with lower positive affect [64,65]. Steeper diurnal cortisol slopes, in turn, are associated with reduced cardiovascular morbidity and mortality [66,67].…”
Section: Potential Pathways Linking Positive Well-being To Cvdmentioning
confidence: 99%
“…Steeper diurnal cortisol slopes, in turn, are associated with reduced cardiovascular morbidity and mortality [66,67]. Some evidence suggests that positive affect is also associated with a less exaggerated increase in cortisol after waking (i.e., cortisol awakening response) [65,68], as well as lower cortisol reactivity to acute laboratory stressors [69]. In addition, during moments when individuals are experiencing more positive affect—relative to their usual levels of positive affect—salivary cortisol levels are reduced [70].…”
Section: Potential Pathways Linking Positive Well-being To Cvdmentioning
confidence: 99%